Analisis Pengaruh Corporate Social Responsibility, Corporate Risk, Capital Intensity Dan Profitability Terhadap Tax Avoidance - Mutiara Kemala Ratu; Vhika Meiriasari (Jurnal Ilmiah Ekonomi Global Masa Kini)
The company's behavior in doing tax avoidance is something that has always been a concern. Tax avoidance is a form of response from the company's management in the tax payment strategy which is still in a legal context. The possibility of tax avoidance by a company, making a good Corporate Governance mechanism as a form of corporate responsibility is considered a solution in overcoming managerial embezzlement. Furthermore, in the policies taken by the company, there are still risks that can arise as a reflection of the policy. Due to the uncertainty in certain conditions, the company's risk is considered to have a role in influencing tax avoidance. Tax avoidance is also expected to be effective because of the investment policy, where companies will have lower tax rates. Similarly, the company's profitability is also considered to have an influence on tax avoidance where there is the ability to generate profits from its business activities, so that the company's profitability will also be higher. From the next problem, this study aims to see how the factors that can encourage tax avoidance by companies, namely corporate social responsibility, corporate risk, capital intensity, and profitability as the main focus in it. The results show that corporate risk and capital intensity are the driving factors for tax avoidance behavior, but not with corporate social responsibility and corporate profitability.Keywords: Tax Avoidance, Corporate Social Responsibility, Corporate Risk, Capital Intensity, Profitabily